Selecting and justifying quantitative analysis techniques in single-case research through a user-friendly open-source tool - Fingerhut, Joelle; Moeyaert, Mariola (Frontiers in Education, 2022)
Certain quantification techniques may be more appropriate than others for single-case design analysis depending on the research questions, the data or graph characteristics, and other desired features. The purpose of this study is to introduce a newly developed and empirically validated user-friendly tool to assist researchers in choosing and justifying single-case design quantification techniques. Different quantification techniques, research questions, data or graph characteristics, and desired features that may affect the appropriateness of a single-case experimental design quantification technique are identified to be included in the tool. The resulting tool provides a ranking of recommended quantification techniques, from most to least appropriate, depending on the user input. A pretest and posttest design was utilized to test the effectiveness of the tool. Results show that those who use single-case designs may need support in choosing and justifying their use of quantification techniques, and that the developed tool can assist in this process. The open-source tool can be downloaded from [link removed for peer-review/ deidentification purposes].